CONCEPT OF SELFMAINTAINING VEHICLES - Filipovic, Srdjan (Journal of Applied Engineering Science, 2020)
Main task of this paper is to present idea of selfmaintaing and make coresponding concept of selfmaintaning vehicles. Through setting parameters of selfmaintaining and providing algorithm of selfmaintenance in vehicles author made attempt to set basic principles in this area of research. Paper presents researched suitability of different drivetrains of vehicles for selfmaintaining. Also, convinient artificial intelligence model for selfmaintaining was reviewed and discussed. Paper discuss near future and future development of maintenance of the vechicles according to presence of mechanical and electrical components. Conclusions made in this papers describes possible ways of future development of maintenance.